STRATEGI PEMBELAJARAN AKTIF: PEMANFAATAN METODE DRILL, TEAMWORK, DAN ROLE PLAY DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Harun, Susanna; Habiburrahim; Silahuddin (Jurnal Tarbiyah Almuslim, 2024)
Islamic Religious Education (PAI) learning has an important role in shaping the character and morality of Muslim individuals. To achieve this goal, an effective learning approach is needed. Effective learning is supported by appropriate learning methods and their impact on student learning outcomes. Some learning methods that can be used are drill, teamwork and role play methods. The drill method is an approach used to strengthen students' understanding of Islamic religious concepts through repeated practice. The teamwork method in PAI learning involves collaboration between students in groups to understand and apply Islamic religious concepts. The role play method in PAI learning involves role simulations where students play certain roles in situations related to the teachings of the Islamic religion. The research results show that the integration of these three methods improves the implementation of learning by creating a more interactive and interesting learning experience, which in turn deepens understanding and strengthens retention of lesson material. This research provides a new contribution to the PAI education literature by showing the potential of interactive learning methods in improving the quality of PAI learning. Carrying out the learning process by determining appropriate methods aims to help students internalize and remember religious information better. Keywords: Drill method, teamwork, role play, PAI learning